Overview of the important factors influencing the performance of eco-friendly brake pads - Irawan, Agustinus Purna; Fitriyana, Deni Fajar; Cionita, Tezara; Siregar, Januar Parlaungan; Laksmidewi, Dwinita; Baskara, Gregorius Dimas; Mohd Zulkifly, Abdullah; Ramli, Junid; Hadi, Agung Efriyo; Mohammad Hazim, Mohamad Hamdan; Najid, Najid (MDPI, 2022)
The braking system is a crucial element in automotive safety. In order for the braking mechanism to function effectively, the brake pads’ durability as well as quality are crucial aspects to take into account. A brake pad is a part of a vehicle that holds the wheel rotation so that braking can occur. Asbestos, which is harmful to human health, is a raw material that is recently being widely used as a material mixture for the manufacturing of brake pads. Many efforts have been made by researchers to find other natural alternative materials to replace the use of asbestos. Natural materials that have received much attention and research include coconut fiber, wood powder or flour, bamboo fiber, shell powder, etc. This review paper focuses on analyzing the main parameters that affect brake pad performance. The composition of filler and fiber types of reinforcement for polymer composites is discussed. Previous studies’ information on the fabrication and testing of brake pads are also highlighted. Furthermore, the findings of this review can provide researchers and academicians with useful information and points to consider for further research.